Method for manufacturing secondary battery and secondary battery
By adjusting the positive and negative potentials of the lithium-ion secondary battery and aging at a specific temperature, the problem of gas generated during use of the battery is solved, and the output performance and life are improved.
Patent Information
- Application Number
- CN202210185212.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-27
- Filing Date
- 2022-02-28
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2042-02-28
AI Technical Summary
Existing non-aqueous electrolyte secondary batteries are prone to gas when used, resulting in battery expansion and reduced electrode reaction field, which in turn affects the performance and life of the battery.
By adjusting the potentials of the positive and negative electrodes to a specific range and maintaining the battery structure at a temperature of 50°C to 90°C, the processing potential adjustment state and aging treatment are achieved, thereby reducing gas generation and battery resistance.
It achieves the effect of high output performance, less circulating gas generated even if it is repeatedly charged and discharged, and has a low battery resistance, which extends the battery life.
Smart Images

Figure CN115249845B_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to a method for manufacturing a secondary battery and a secondary battery. Background Art
[0002] In recent years, as high energy density batteries, research and development of secondary batteries such as non-aqueous electrolyte secondary batteries like lithium ion secondary batteries have been actively carried out. Non-aqueous electrolyte secondary batteries and other secondary batteries are expected to be used as power sources for vehicles such as hybrid electric vehicles and electric vehicles, and for uninterruptible power supplies of mobile phone base stations. Therefore, in addition to high energy density, secondary batteries are also required to have excellent other performances such as fast charge and discharge performance and long-term reliability.
[0003] As a commercially available non-aqueous electrolyte secondary battery, for example, a battery can be cited that uses a lithium transition metal composite oxide containing Co, Mn, Ni, etc. as a positive electrode active material and uses a carbonaceous material or a titanium-containing oxide, etc. as a negative electrode active material.
[0004] If moisture is contained in a non-aqueous electrolyte secondary battery, gases can be generated from the moisture during battery operation. As gases from moisture, for example, hydrogen and oxygen can be cited. When a large amount of gas is generated inside the battery, the battery expands. In addition, if gas exists on the surface of the electrode active material, that part no longer comes into contact with the non-aqueous electrolyte, so the electrode reaction field decreases. As a result, the current load on the remaining electrode interface becomes larger and the battery resistance increases.
[0005] In order to remove moisture when manufacturing a non-aqueous electrolyte secondary battery, for example, heating and drying are performed before introducing an electrolyte into a battery container, or battery production is carried out under environmental conditions with less water vapor such as an environment with a low dew point. Even after such treatment, moisture may remain inside the battery container, or a trace amount of moisture may be mixed into the non-aqueous electrolyte.
[0006] As a means of preventing the generation of gases from residual moisture during battery use, charge and discharge or aging treatment is performed in advance during battery manufacturing to remove the gases generated at this time. For example, the battery container is temporarily sealed, charged to a specified state of charge (SOC), aged under a specific temperature environment for a certain period in this charged state, then the temporary seal is released in a vacuum environment to release the gases generated during aging, and formal sealing is performed again.
[0007] In addition, depending on the battery configuration such as the composition of the electrolyte and the aging conditions, a coating film may sometimes be formed on the electrode. It is known that with the repeated use of a secondary battery, the positive electrode active material or the negative electrode active material deteriorates, and the deterioration such as a decrease in the capacity of the secondary battery becomes more pronounced. As one of the causes of the deterioration, for example, the reaction between the active material and the electrolytic solution (liquid electrolyte) can be cited. There is a known technique of forming the above-mentioned coating film, for example, forming a coating film on the surface of the active material, and using this coating film to prevent the decomposition (side reaction) of the electrolytic solution, thereby suppressing the deterioration of the battery characteristics. Summary of the Invention
[0008] According to an embodiment, there is provided a method for manufacturing a secondary battery, which includes the following steps: a step of preparing a battery structure including a positive electrode, a negative electrode, and an electrolyte; a step of obtaining a processed potential adjustment state by adjusting the positive electrode potential of the positive electrode to be in the range of 3.4 V to 3.9 V based on the oxidation-reduction potential of lithium and adjusting the negative electrode potential of the negative electrode to be in the range of 1.5 V to 2.0 V based on the oxidation-reduction potential of lithium; and a step of maintaining the battery structure in the processed potential adjustment state at a holding temperature in the range of 50 °C to 90 °C. The positive electrode contains a lithium nickel cobalt manganese composite oxide. The negative electrode contains a niobium titanium composite oxide. The electrolyte contains one or more first organic solvents having a viscosity of 1 cP or less.
[0009] According to another embodiment, there is provided a secondary battery manufactured by the manufacturing method of the above embodiment.
[0010] Based on the above, it is possible to provide a method for manufacturing a secondary battery that can obtain a secondary battery with high output performance and little gas generation even after repeated charge and discharge cycles, and a low-resistance secondary battery with high output performance and little gas generation even after repeated charge and discharge cycles. Brief Description of the Drawings
[0011] Figure 1 It is a cross-sectional view schematically showing an example of the battery structure of the embodiment.
[0012] Figure 2 It is to Figure 1 A cross-sectional view obtained by magnifying part A of the battery structure shown.
[0013] Figure 3 It is a partial cutaway perspective view schematically showing another example of the battery structure of the embodiment.
[0014] Figure 4 It is to Figure 3 A cross-sectional view obtained by magnifying part B of the battery structure shown.
[0015] Figure 5 It is a cross-sectional view schematically showing still another example of the battery structure of the embodiment.
[0016] Figure 6 is a schematic cross-sectional view along the VI-VI line of the battery structure shown below. Figure 5 shown in the figure.
[0017] Symbol Explanation
[0018] 1 Electrode group, 2 Outer packaging member, 3 Negative electrode, 3a Negative electrode current collector, 3b Negative electrode active material layer-containing layer, 4 Separator, 5 Positive electrode, 5a Positive electrode current collector, 5b Positive electrode active material layer-containing layer, 6 Negative terminal, 7 Positive terminal, 8 Negative electrode gasket, 9 Positive electrode gasket, 10 Sealing plate, 11 Control valve, 16 Negative electrode lead wire, 17 Positive electrode lead wire, 18 Liquid injection port, 19 Sealing plug, 100 Battery structure. Detailed Embodiment
[0019] Hereinafter, the embodiments will be described with appropriate reference to the drawings. In addition, the same reference numerals are used for the common components throughout the embodiments, and the repeated descriptions are omitted. In addition, each drawing is a schematic diagram for facilitating the description and understanding of the embodiments, and its shape, size, ratio, etc. are different from those of the actual device, but these can be appropriately designed and changed with reference to the following description and well-known techniques.
[0020] [First Embodiment]
[0021] According to the first embodiment, a method for manufacturing a secondary battery is provided. The manufacturing method includes: a step of preparing a battery structure, a step of obtaining a processed potential adjustment state, and a step of maintaining the battery structure in the processed potential adjustment state at a holding temperature in the range of 50°C to 90°C. The battery structure includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode contains a lithium nickel cobalt manganese composite oxide. The negative electrode contains a niobium titanium composite oxide. The electrolyte contains one or more first organic solvents having a viscosity (η) of 1 cP or less. The processed potential adjustment state is obtained by adjusting the positive electrode potential of the positive electrode to be in the range of 3.4 V to 3.9 V based on the oxidation-reduction potential of lithium, and adjusting the negative electrode potential of the negative electrode to be in the range of 1.5 V to 2.0 V based on the oxidation-reduction potential of lithium.
[0022] As a means for improving the output performance under low-temperature conditions, it is possible to increase the amount of the low-viscosity solvent contained in the electrolyte. Examples of the low-viscosity solvent include propionate esters such as ethyl propionate (EP) and methyl ethyl carbonate (MEC). However, EP and MEC are thermally weak. Therefore, when the proportion of EP and MEC increases, gas is likely to be generated in a high-temperature environment of about 70°C to 80°C, for example. For example, in-vehicle batteries mounted on vehicles such as electric vehicles, hybrid electric vehicles, and railway vehicles are required to exhibit good performance in both low-temperature and high-temperature environments.
[0023] By subjecting a battery containing EP and MEC to an aging treatment, the amount of gas can be significantly reduced. On the contrary, however, it has been found that the battery resistance increases when aging is performed. As a result of intensive studies by the present inventors, it has been found that the battery resistance increases when aging is performed under a high state of charge (SOC), for example, under the condition of SOC 100%. In contrast, it has been found that the increase in resistance can be suppressed by performing aging under a low SOC. Thus, through aging, the tendency for the resistance to increase under a high SOC and for the increase in resistance to disappear under a low SOC is independent of the additives in the electrolyte. Therefore, it is considered that easily destructible solvents such as EP and MEC decompose under high SOC conditions and become the main cause of the increase in resistance.
[0024] The manufacturing method of the secondary battery according to the first embodiment includes: maintaining a battery structure using an electrolyte containing a first organic solvent having a viscosity η of less than 1 cP at a holding temperature within the above specific range in a processed potential adjustment state, where the processed potential adjustment state is obtained by adjusting the positive electrode potential to 3.4 V to 3.9 V (vs. Li / Li + ) and simultaneously adjusting the negative electrode potential to 1.5 V to 2.0 V (vs. Li / Li + ). The battery structure corresponds to a precursor of the secondary battery. Moreover, the treatment of maintaining the battery structure in the processed potential adjustment state at the above holding temperature corresponds to so-called aging. In addition, the above processed potential adjustment state corresponds to a low state of charge (SOC) of a battery in which a lithium nickel cobalt manganese composite oxide is contained as an active material in the positive electrode and a niobium titanium composite oxide is contained as an active material in the negative electrode. That is, the manufacturing method of this secondary battery includes aging under low SOC conditions. By performing aging under a low SOC, the decomposition of the first organic solvent including EP and MEC can be suppressed. Thereby, the generation of gas during battery use and the increase in battery resistance can be suppressed. A battery with a lower battery resistance can exhibit high output performance. Even when the battery manufactured by this manufacturing method is repeatedly subjected to charge and discharge cycles under high temperature conditions (for example, around 70°C to 80°C), the generation of gas can be suppressed to a small amount.
[0025] Therefore, according to the manufacturing method of the first embodiment, a secondary battery that exhibits high output performance from low temperature to high temperature and has excellent life performance even under high temperature conditions can be manufactured.
[0026] The process of adjusting the positive electrode potential and the negative electrode potential to the above ranges to obtain the processing potential adjustment state, and the process of maintaining the battery structure at the above holding temperature in the processing potential adjustment state are sometimes collectively referred to as the "pretreatment" of the secondary battery manufactured by the manufacturing method of the first embodiment. Through this pretreatment, gas is pre-generated at the manufacturing stage of the secondary battery, thereby reducing the amount of gas that can be generated during battery use. The gas pre-generated through the pretreatment is removed before the completion of the manufacturing of the secondary battery. For example, the gas generated during the pretreatment contains gas from residual moisture (such as hydrogen, oxygen). Therefore, by performing exhaust after the pretreatment, the residual moisture can be reduced. The details of the exhaust will be described later.
[0027] The battery structure adjusted to the processing potential adjustment state is maintained at a holding temperature of 50°C to 90°C. By making the holding temperature 50°C or higher, the reaction of pre-generating gas during the pretreatment can be promoted. By making the holding temperature 90°C or lower, excessive decomposition of the first organic solvent can be suppressed, and thus an increase in battery resistance can be suppressed.
[0028] The time for maintaining the battery structure at the above holding temperature is preferably 6 hours to 72 hours. By maintaining for 6 hours or more, the amount of gas generated during the use of the secondary battery can be further reduced. By keeping the upper limit of the holding time at 72 hours, excessive decomposition of electrolyte components such as the first organic solvent can be avoided.
[0029] The battery structure includes a positive electrode, a negative electrode, and an electrolyte. The details of each of the positive electrode, negative electrode, and electrolyte will be described later. The battery structure may further include a separator disposed between the positive electrode and the negative electrode. The negative electrode, positive electrode, and separator may form an electrode assembly. The electrolyte may be held in the electrode assembly.
[0030] In addition, the battery structure may further include an outer packaging member that houses the electrode assembly and the electrolyte.
[0031] Moreover, the battery structure may further include a negative terminal electrically connected to the negative electrode and a positive terminal electrically connected to the positive electrode.
[0032] The battery structure can be prepared, for example, by housing the positive electrode, negative electrode, and electrolyte in the outer packaging member. The manufacturing method of the positive electrode, the manufacturing method of the negative electrode, and the adjustment method of the electrolyte will be described later respectively. The preparation of the battery structure is preferably carried out in an inert atmosphere. In addition, the preparation of the battery structure is preferably carried out in a dry environment. By using an inert atmosphere and a dry environment, oxygen, carbon dioxide, hydrogen, etc. that can be gas generation sources can be avoided. Regarding the manufacturing of the positive and negative electrodes and the adjustment of the electrolyte, it is also preferably carried out in an inert atmosphere and a dry environment. As an inert atmosphere, for example, an argon atmosphere can be cited.
[0033] The form of the electrode group is not particularly limited. For example, it may have a wound structure or a laminated structure.
[0034] The wound-type electrode group can be produced as follows, for example. The positive electrode and the negative electrode are laminated in such a way that a separator is sandwiched between them to obtain a laminate of the positive electrode, the negative electrode, and the separator. After winding the laminate, by further applying pressure to the obtained wound body, a flat wound-type electrode group can be produced.
[0035] The laminated-type electrode group can be produced, for example, by laminating the positive electrode, the negative electrode, and the separator in such a way that a separator is sandwiched between the positive electrode and the negative electrode. Here, a plurality of separators can be respectively arranged between the positive electrode and the negative electrode, or a single separator can be bent, for example, and the positive electrode and the negative electrode can be alternately arranged in the space formed by folding back the separator.
[0036] The battery structure is produced by placing the electrode group and the electrolyte in an outer packaging member and performing temporary sealing. Details will be described later. As the outer packaging member, for example, a container made of a laminated film or a metal container can be used. Details of the outer packaging member will be described later.
[0037] In the case of using an outer packaging member made of a laminated film, for example, the opening can be closed by heat fusion bonding to perform temporary sealing. At the time of temporary sealing, for example, the position that is more outside (closer to the opening end) than the position where the formal sealing is performed in the secondary battery as a manufactured product is closed by heat fusion bonding.
[0038] In the case of using a metal container as the outer packaging member, for example, the temporary sealing can be performed by plugging the liquid injection port provided outside the container for introducing the electrolyte. The liquid injection port can be provided, for example, on the lid of the metal container such as a sealing plate. For example, after putting the liquid electrolyte into the metal container through the liquid injection port, the temporary sealing is performed by installing a rubber plug on the liquid injection port.
[0039] The method of performing temporary sealing is not limited to the above examples.
[0040] The adjustment of the positive and negative electrode potentials to the processing potential adjustment state can be performed, for example, by subjecting the temporarily sealed battery structure to the first charge and discharge. In order to make the potentials of the positive electrode and the negative electrode respectively fall within the potential range in the above-mentioned processing potential adjustment state, charge and discharge are performed to obtain an appropriate state of charge (SOC). The SOC can be adjusted according to the battery voltage, for example. According to the active materials respectively used for the positive electrode and the negative electrode and the design of each electrode, the first charge and discharge is performed to an appropriate SOC to make the battery structure in the processing potential adjustment state. For example, for a battery containing LiNi used as the positive electrode active material 0.5 Co0.3 Mn 0.2 O 2 The positive electrode of the lithium nickel cobalt manganese composite oxide represented by and the negative electrode using Nb as the negative electrode active material 2 TiO 7 and a battery structure (or secondary battery) manufactured in such a way that the charge capacities of the positive and negative electrode active materials are positive electrode:negative electrode = 1:1. When the battery voltage is 1.8 V, the positive electrode potential is 3.65 V (vs. Li / Li + ) and the negative electrode potential is 1.85 V (vs. Li / Li + ). Under this condition, the SOC is 10%. The battery structure can be brought into a processed potential adjustment state by the first charge, or for example, it can also be brought into a processed potential adjustment state by the first discharge after the first charge until the full charge state (SOC 100%).
[0041] Alternatively, before assembling the battery structure, the positive and negative electrodes can be charged and discharged separately to obtain a processed potential adjustment state. For example, a battery (such as a half-cell) can be assembled using the positive electrode and a counter electrode made of lithium metal to adjust the positive electrode potential. Similarly, a battery (such as a half-cell) can be assembled using the negative electrode and a counter electrode made of lithium metal to adjust the negative electrode potential. By manufacturing a battery structure using the positive and negative electrodes whose potentials have been adjusted separately, a battery structure in a processed potential adjustment state can be obtained.
[0042] The charge and discharge for obtaining the processed potential adjustment state are performed, for example, at room temperature (such as around 25 °C).
[0043] The battery structure in the processed potential adjustment state is maintained at a temperature of 50 °C to 90 °C. For example, the battery structure in the processed potential adjustment state is placed in a thermostatic bath set at 50 °C to 90 °C. For the purpose of maintaining temperature management and control, a temperature sensor can also be connected to the surface of the battery structure. After a certain period of time, the battery structure is taken out of the thermostatic bath and cooled to room temperature, for example.
[0044] The temporary seal is opened to release the gas generated by the pretreatment. After exhausting the gas, the outer packaging member is formally sealed to obtain a secondary battery. For example, after cooling the battery structure taken out of the thermostatic bath to room temperature, the battery structure is placed in an inert atmosphere and the temporary seal is opened. A secondary battery can be obtained by formally sealing the outer packaging member under a reduced pressure environment. Alternatively, after opening the temporary seal under a reduced pressure environment, a secondary battery can be obtained by formally sealing the outer packaging member. The reduced pressure environment mentioned here refers to, for example, a vacuum state of around -90 kPa.
[0045] In the case of using an outer packaging member made of a laminated film, for example, the outer packaging member can be opened by cutting it at the position where the temporary seal is applied, or by cutting off the portion of the outer packaging member where the temporary seal is applied. For the permanent seal of the outer packaging member made of a laminated film, for example, the opening formed by opening can be closed by heat fusion bonding. The permanent seal of the outer packaging member is preferably performed at a position closer to the inside (a position farther from the opening end) than the position where the temporary seal is applied.
[0046] In the case of using a metal container as the outer packaging member, for example, the outer packaging member can be opened by removing the sealing plug used for temporary sealing. On the opening formed by removing the plug (for example, the electrolyte injection port), for example, the metal container can be permanently sealed by welding a sealing plug made of a material that can be welded to the container.
[0047] It is also possible to perform charge and discharge after the treatment of maintaining the temperature, and adjust to the charging state for the secondary battery to leave the factory. The charge and discharge in the factory state can be performed, for example, before opening the temporary seal and exhausting the gas, or can also be performed after the permanent seal of the secondary battery. In addition, after the permanent seal, it is also possible to perform capacity confirmation based on the charge and discharge of the secondary battery for confirming the quality as a product, running-in charge and discharge of the secondary battery, etc.
[0048] Specific examples will be described. Here, as an outer packaging member made of a laminated film, an example of using a laminated box will be described.
[0049] An electrode group is made using a positive electrode and a negative electrode, and the electrode group is housed in a laminated box. After injecting the electrolyte into the laminated box under an argon atmosphere, a temporary seal is applied by heat fusion bonding under reduced pressure. The first charge and discharge are performed, and the potentials of the positive and negative electrodes are adjusted by setting the battery voltage to a specified voltage. The battery structure with the adjusted electrode potential is placed in a constant temperature bath at a specified temperature, taken out of the constant temperature bath after a certain period of time, and then placed again in an argon atmosphere. The upper part of the laminated box is opened, and heat fusion bonding is performed again at a portion closer to the inside under reduced pressure for permanent sealing.
[0050] Hereinafter, the positive electrode, negative electrode, electrolyte, separator, outer packaging member, negative terminal, and positive terminal will be described in detail.
[0051] (1) Positive electrode
[0052] The positive electrode contains a lithium nickel cobalt manganese composite oxide as a positive electrode active material. The positive electrode may include a positive electrode active material-containing layer containing the positive electrode active material. The positive electrode may also include a positive electrode current collector.
[0053] The positive electrode active material-containing layer can be formed on one side or both sides of the positive electrode current collector. The positive electrode active material-containing layer may optionally contain a conductive agent and a binder in addition to the positive electrode active material.
[0054] As a specific example of the above lithium nickel cobalt manganese composite oxide, a compound represented by x Li 1-y-z Ni y Co z Mn 2 O
[0055] The positive electrode active material may contain other compounds in addition to the above lithium nickel cobalt manganese composite oxide. Here, for convenience, the above lithium nickel cobalt manganese composite oxide is referred to as the first positive electrode active material, and other compounds as the positive electrode active material are referred to as the second positive electrode active material. The positive electrode active material may contain one or more first positive electrode active materials and one second positive electrode active material together, or may also contain one or more first positive electrode active materials and two or more second positive electrode active materials together. The positive electrode active material contains the first positive electrode active material (the above lithium nickel cobalt manganese composite oxide) at a ratio of 70% by mass or more, preferably 90% by mass or more. The positive electrode active material may also contain only the first positive electrode active material (the above lithium nickel cobalt manganese composite oxide).
[0056] Examples of the second positive electrode active material include, for example, manganese dioxide (MnO 2 ), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (for example, a compound represented by Li x Mn 2 O 4 or Li x MnO 2 and 0 < x ≤ 1), lithium nickel composite oxide (for example, a compound represented by Li x NiO 2 and 0 < x ≤ 1), lithium cobalt composite oxide (for example, a compound represented by Li x CoO 2 and 0 < x ≤ 1), lithium nickel cobalt composite oxide (for example, a compound represented by Li x Ni 1-y Co y O 2 and 0 < x ≤ 1 and 0 < y < 1), lithium manganese cobalt composite oxide (for example, a compound represented by Li x Mn y Co 1-y O 2 and 0 < x ≤ 1 and 0 < y < 1), lithium manganese nickel composite oxide having a spinel structure (for example, a compound represented by Li x Mn2-w Ni w O 4 A compound represented by and where 0 < x ≤ 1 and 0 < w < 2), a lithium phosphide having an olivine structure (e.g., represented by Li x FePO 4 A compound represented by and where 0 < x ≤ 1; represented by Li x Fe 1-y Mn y PO 4 A compound represented by and where 0 < x ≤ 1 and 0 < y ≤ 1; represented by Li x CoPO 4 A compound represented by and where 0 < x ≤ 1), iron sulfate (Fe 2 (SO 4 ) 3 ) and vanadium oxide (e.g., V 2 O 5 ).
[0057] When using a room temperature molten salt as the electrolyte of the battery, it is preferable to use a positive electrode active material containing lithium iron phosphate, a compound represented by Li v VPO 4 F and where 0 ≤ v ≤ 1, a lithium manganese composite oxide, a lithium nickel composite oxide, a lithium nickel cobalt composite oxide, or a mixture thereof. Since the reactivity of the above compounds with the room temperature molten salt is low, the cycle life can be improved. Details of the room temperature molten salt will be described later.
[0058] The primary particle size of the positive electrode active material is preferably 100 nm to 10 μm. A positive electrode active material with a primary particle size of 100 nm or more is easy to handle in industrial production. A positive electrode active material with a primary particle size of 100 μm or less allows for smooth diffusion of lithium ions within the solid.
[0059] The specific surface area of the positive electrode active material is preferably 0.1 m 2 / g to 10 m 2 / g. A positive electrode active material with a specific surface area of 0.1 m 2 / g or more can sufficiently ensure the insertion and extraction of Li ions. A positive electrode active material with a specific surface area of 10 m 2 / g or less is easy to handle in industrial production and can ensure good charge-discharge cycle performance.
[0060] Here, the specific surface area is measured by adsorbing molecules with a known adsorbed occupancy area on the surface of powder particles at the temperature of liquid nitrogen, and calculating the specific surface area of the sample from the amount thereof. The most commonly used is the BET method based on the physical adsorption of inert gases at low temperature and low humidity. This BET method is a method based on the BET theory, which is the most well-known theory for calculating the specific surface area by extending the monolayer adsorption theory, i.e., the Langmuir theory, to multilayer adsorption. The specific surface area obtained thereby is called the BET specific surface area.
[0061] The conductive agent is added to improve the current collection performance of the positive electrode active material and suppress the contact resistance with the positive electrode current collector. Examples of the conductive agent include acetylene black, carbon black, graphite, carbon fiber, graphene, carbon nanotube, carbon nanofiber, and fullerene. One of them can be used as the conductive agent, or two or more of them can be combined and used as the conductive agent. Additionally, the conductive agent can be omitted.
[0062] The binder is added to bond the positive electrode active material and the conductive agent. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, polyacrylonitrile, and polyethylene oxide. One of them can be used as the binder, or two or more of them can be combined and used as the binder.
[0063] The proportions of the positive electrode active material, conductive agent, and binder contained in the positive electrode active material layer are preferably set to 80% by mass to 95% by mass, 3% by mass to 18% by mass, and 1% by mass to 17% by mass, respectively. By setting the amount of the conductive agent to 3% by mass or more, the above effects can be exerted. By setting the amount of the conductive agent to 18% by mass or less, the decomposition of the electrolyte on the surface of the conductive agent during high-temperature storage can be reduced. By setting the amount of the binder to 1% by mass or more, sufficient positive electrode strength can be obtained. By setting the amount of the binder to 17% by mass or less, the amount of the insulating material, i.e., the binder, in the positive electrode can be reduced, and the internal resistance can be decreased.
[0064] The positive electrode current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu, and Si.
[0065] The thickness of the aluminum foil or aluminum alloy foil is preferably 50 μm to 200 μm, more preferably 150 μm or less. The purity of the aluminum foil is preferably 99% by mass or more. The contents of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil are preferably 1% by mass or less.
[0066] In addition, the positive electrode current collector may have a portion where the positive electrode active material layer is not formed on its surface. This portion can function as a current collector tab.
[0067] The positive electrode can be fabricated, for example, by the following method. First, a slurry is prepared by suspending a positive electrode active material, a conductive agent, and a binder in a solvent. The slurry is coated on one or both sides of a positive electrode current collector. Then, the coated slurry is dried to obtain a laminate including a positive electrode active material layer and the current collector. Next, pressure is applied to this laminate. Thus, the positive electrode is fabricated.
[0068] Alternatively, the positive electrode can also be fabricated by the following method. First, a positive electrode active material, a conductive agent, and a binder are mixed to obtain a mixture. Next, the mixture is formed into granular shape. Then, by disposing these granules on a positive electrode current collector, the positive electrode can be obtained.
[0069] (2) Negative electrode
[0070] The negative electrode contains a niobium-titanium composite oxide as a negative electrode active material. The negative electrode may include a negative electrode active material layer containing the negative electrode active material. The negative electrode may also contain a negative electrode current collector.
[0071] The negative electrode active material layer may be formed on one or both sides of the negative electrode current collector. The negative electrode active material layer may optionally contain a conductive agent and a binder in addition to the negative electrode active material.
[0072] The crystal structure of the niobium-titanium composite oxide may be, for example, monoclinic. When the negative electrode active material contains a monoclinic niobium-titanium composite oxide, in addition to excellent energy density, high rate performance can also be achieved. Taking one of the monoclinic niobium-titanium composite oxides, i.e., Nb 2 TiO 7 as an example to illustrate the reason. In the crystal structure of Nb 2 TiO 7 , the equivalent intercalation space for lithium ions is large and the structure is stable, and there are regions with two-dimensional channels where lithium ions diffuse rapidly and a conduction path in the
[001] direction connecting them. Thus, in the crystal structure of the monoclinic niobium-titanium composite oxide Nb 2 TiO 7 , the intercalation / deintercalation property of lithium ions into the intercalation space can be improved, and at the same time, the intercalation / deintercalation space for lithium ions actually increases. Thereby, high capacity and high rate performance can be provided.
[0073] Examples of the monoclinic niobium-titanium composite oxide include those composed of Li a Ti 1-b M1 b Nb 2-c M2 c O 7+δThe represented compound. Among them, M1 is at least one selected from Zr, Si, and Sn. M2 is at least one selected from V, Ta, and Bi. Each subscript in the compositional formula is 0 ≤ a ≤ 5, 0 ≤ b < 1, 0 ≤ c < 2, -0.3 ≤ δ ≤ 0.3. As a specific example of the monoclinic niobium-titanium composite oxide, Li can be cited. a Nb 2 TiO 7 (0 ≤ a ≤ 5).
[0074] As other examples of the monoclinic niobium-titanium composite oxide, those represented by Li a Ti 1-b M3 b+c Nb 2-c O 7-δ can be cited. Among them, M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo. Each subscript in the compositional formula is 0 ≤ a ≤ 5, 0 ≤ b < 1, 0 ≤ c < 2, -0.3 ≤ δ ≤ 0.3.
[0075] As specific examples of the niobium-titanium composite oxide, for example, Nb 2 TiO 7 、Nb 2 Ti 2 O 9 、Nb 10 Ti 2 O 29 、Nb 14 TiO 37 and Nb 24 TiO 62 can be cited. The niobium-titanium composite oxide can be a substituted niobium-titanium composite oxide obtained by substituting at least a part of Nb and / or Ti with foreign elements. Examples of the substitution elements include Na, k, Ca, Co, Ni, Si, P, V, Cr, Mo, Ta, Zr, Mn, Fe, Mg, B, Pb, and Al, etc. The substituted niobium-titanium composite oxide can contain one substitution element or two or more substitution elements.
[0076] The niobium-titanium composite oxide can contain a titanium-niobium composite oxide having an orthorhombic crystal structure. As an example of the titanium-niobium composite oxide having an orthorhombic structure, those represented by Li 2+d Na 2-e M4 f Ti 6-g- h Nb g M5 h O 14+σ can be cited. In the general formula Li 2+d Na 2-e M4f Ti 6-g-h Nb g M5 h O 14+σ In the formula, the subscript d is in the range of 0 ≤ d ≤ 4, the subscript e is in the range of 0 < e < 2, the subscript f is in the range of 0 ≤ f < 2, the subscript g is in the range of 0 < g < 6, the subscript h is in the range of 0 ≤ h < 3, the sum of the subscripts g and h is in the range of 0 < g + h < 6, and the subscript σ is in the range of -0.5 ≤ σ ≤ 0.5. The element M4 is at least one selected from Cs, K, Sr, Ba, and Ca. The element M5 is at least one selected from Zr, Sn, V, Ta, Mo, W, Fe, Mn, and Al.
[0077] Regarding the niobium-titanium composite oxide with respect to the above compositional formula or general formula, the element ratio of niobium to other elements can also deviate from the theoretical value. For example, compared with the theoretical value of niobium and other elements, the amount of niobium is preferably larger. In this way, when adjusting the negative electrode potential, niobium ions dissolve from the negative electrode into the electrolyte during the initial charging, promoting the uniform formation of the sulfur-containing coating film on the surface of the negative electrode. Therefore, there is a tendency to obtain a negative electrode with excellent high-temperature resistance.
[0078] The negative electrode active material may contain one of the above niobium-titanium composite oxides alone, or may contain two or more of the above in combination.
[0079] In addition to the niobium-titanium composite oxide, the negative electrode active material may also contain other compounds. Here, for convenience, the niobium-titanium composite oxide is referred to as the first negative electrode active material, and other compounds as the negative electrode active material are referred to as the second negative electrode active material. The negative electrode active material may contain one or more first negative electrode active materials and one second negative electrode active material together, or may contain one or more first negative electrode active materials and two or more second negative electrode active materials together. The negative electrode active material contains the first negative electrode active material (niobium-titanium composite oxide) in a proportion of 70% by mass or more, preferably 90% by mass or more. The negative electrode active material may also contain only the first negative electrode active material (niobium-titanium composite oxide).
[0080] Examples of the second negative electrode active material include lithium titanate having an orthorhombic manganese ore structure (e.g., Li 2+ m Ti 3 O 7 , 0 ≤ m ≤ 3), lithium titanate having a spinel structure (e.g., Li 4+m Ti 5 O 12 , 0 ≤ m ≤ 3), titanium dioxide (TiO 2 ), anatase-type titanium dioxide, rutile-type titanium dioxide, niobium pentoxide (Nb 2 O5 ) Orthorhombic titanium composite oxides other than the todorokite-type titanium composite oxide and the above-described orthorhombic titanium-niobium composite oxide.
[0081] Examples of orthorhombic titanium composite oxides other than the orthorhombic titanium-niobium composite oxide include compounds represented by Li 2+n M6 2-p Ti 6-q M7 r O 14+σ . Among them, M6 is at least one selected from Sr, Ba, Ca, Mg, Na, Cs, Rb, and K. M7 is at least one selected from Zr, Sn, V, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni, and Al. Each subscript in the composition formula is 0 ≤ n ≤ 6, 0 ≤ p < 2, 0 ≤ q < 6, 0 ≤ r < 6, -0.5 ≤ σ ≤ 0.5. Specific examples of orthorhombic titanium-containing composite oxides include Li 2+n Na 2 Ti 6 O 14 (0 ≤ n ≤ 6).
[0082] The negative electrode active material can be contained in the negative electrode active material-containing layer in the form of particles, for example. The negative electrode active material particles can take the form of primary particles, or can take the form of secondary particles formed by aggregation of primary particles. The negative electrode active material particles can also be a mixture of primary particles and secondary particles.
[0083] The average particle diameter (D 50 ) of the negative electrode active material particles is, for example, in the range of 0.1 μm to 50 μm. The average particle diameter can vary according to the required battery performance. For example, in order to improve the fast charge-discharge performance, it is preferable that the average particle diameter is 5.0 μm or less. In this way, the diffusion distance of lithium ions in the crystal can be reduced, so the fast charge-discharge performance can be improved. The average particle diameter can be determined by, for example, the laser diffraction method. The average particle diameter means, for example, the median diameter d 50 obtained by the laser diffraction scattering method.
[0084] Whether the negative electrode active material contains secondary particles or primary particles can be determined by observation with a scanning electron microscope (SEM: Scanning Electron Microscopy). In addition, the average primary particle diameter and the average secondary particle diameter of the active material particles can be measured by SEM observation.
[0085] The BET (Brunauer, Emmett, Teller) specific surface area of the negative electrode active material is not particularly limited. However, the BET specific surface area is preferably 0.1 m2 / g to 20 m 2 / g, more preferably 1 m 2 / g to 10 m 2 / g.
[0086] If the specific surface area is 0.1 m 2 / g or more, the contact area with the electrolyte can be ensured, and it is easy to obtain good discharge rate performance, and the charging time can be shortened. On the other hand, if the specific surface area is 20 m 2 / g or less, the reactivity with the electrolyte will not become too high, and the life performance can be improved. In addition, the coatability of the slurry containing the negative electrode active material used in the manufacture of the electrode described later can be made good.
[0087] The conductive agent is added to improve the current collection performance and suppress the contact resistance between the active material and the current collector. Examples of the conductive agent include carbonaceous materials such as vapor grown carbon fiber (VGCF), carbon black such as acetylene black, graphite, carbon nanotubes, and carbon nanofibers. One of them can be used as the conductive agent, or two or more of them can be used in combination as the conductive agent. Alternatively, carbon coating or electron-conductive inorganic material coating can be applied to the surface of the active material particles instead of using the conductive agent. In addition, covering the surface of the active material with carbon or a conductive material while using the conductive agent can also improve the current collection performance of the active material-containing layer.
[0088] The binder is added to fill the gaps between the dispersed active materials and bond the negative electrode active material and the negative electrode current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, styrene-butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of them can be used as the binder, or two or more of them can be used in combination as the binder.
[0089] In the negative electrode active material-containing layer, the negative electrode active material, the conductive agent, and the binder preferably contain 70% to 96% by mass, 2% to 28% by mass, and 2% to 28% by mass, respectively. By making the amount of the conductive agent 2% by mass or more, the current collection performance of the negative electrode active material-containing layer can be improved, and the high-current performance of the secondary battery can be improved. In addition, by making the amount of the binder 2% by mass or more, the adhesion between the negative electrode active material-containing layer and the current collector can be improved, and the cycle performance can be improved. On the other hand, setting the conductive agent and the binder to 28% by mass or less is preferable in terms of pursuing high capacity.
[0090] The density of the negative electrode active material layer (excluding the current collector) is preferably 1.8 g / cm 3 ~3.5 g / cm 3 . The negative electrode with the density of the negative electrode active material layer within this range is excellent in terms of energy density and electrolyte retention. The density of the negative electrode active material layer is more preferably 2.1 g / cm 3 ~3.0 g / cm 3 .
[0091] The negative electrode current collector uses a material that is electrochemically stable at the potential for insertion and extraction of lithium (Li) into and from the negative electrode active material. The negative electrode current collector is preferably made of, for example, copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the negative electrode current collector is preferably 5 μm to 20 μm. A negative electrode current collector having such a thickness can achieve a balance between the strength and light weight of the negative electrode.
[0092] In addition, the negative electrode current collector may have a portion where the negative electrode active material layer is not formed on its surface. This portion can function as a current collector tab.
[0093] The negative electrode can be produced, for example, by the following method. First, a slurry is prepared by suspending the negative electrode active material, the conductive agent, and the binder in a solvent. The slurry is coated on one or both sides of the negative electrode current collector. Then, the coated slurry is dried to obtain a laminate of the negative electrode active material layer and the current collector. Then, the laminate is pressed. Thus, the negative electrode is fabricated.
[0094] Alternatively, the negative electrode can also be produced by the following method. First, the negative electrode active material, the conductive agent, and the binder are mixed to obtain a mixture. Then, the mixture is formed into granular form. Then, by arranging these granules on the negative electrode current collector, the negative electrode can be obtained.
[0095] (3) Electrolyte
[0096] As the electrolyte, for example, a liquid non-aqueous electrolyte or a gel-like non-aqueous electrolyte can be used. The liquid non-aqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in a liquid solvent such as an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L to 2.5 mol / L.
[0097] Examples of the electrolyte salt include lithium perchlorate (LiClO 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiCF 3 SO3 ), and lithium salts such as lithium bis(trifluoromethanesulfonyl)imide (LiN(CF 3 SO 2 )) 2 ), and mixtures thereof. The electrolyte salt is preferably an electrolyte salt that is not easily oxidized even at high potentials, and most preferably LiPF 6 .
[0098] The solvent of the electrolyte contains at least one or more first organic solvents having a viscosity η of 1 cP or less. Examples of the first organic solvent include chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); and propionate esters such as methyl propionate, ethyl propionate (EP), propyl propionate, and butyl propionate; cyclic ethers such as tetrahydrofuran (THF), 2-methyltetrahydrofuran (2Me THF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); and acetonitrile (AN). These first organic solvents can be used alone or as a mixed solvent. The first organic solvent preferably contains one or more selected from diethyl carbonate, methyl ethyl carbonate, and ethyl propionate. In addition, the viscosity (η) of methyl ethyl carbonate is 0.65 cP, and the viscosity of ethyl propionate is 0.533 cP.
[0099] In addition to the above-mentioned first organic solvent, the electrolyte may further contain a second organic solvent having a viscosity η exceeding 1 cP. Examples of the second organic solvent include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); γ-butyrolactone (GBL), and sulfolane (SL). The electrolyte may contain one or more of the first organic solvents and one of the above-mentioned second organic solvents at the same time, or the electrolyte may also contain one or more of the first organic solvents and two or more of the second organic solvents at the same time. As the second organic solvent, propylene carbonate is preferably contained. In addition, the viscosity (η) of propylene carbonate is 2.53.
[0100] The volume ratio of the first organic solvent in the electrolyte is preferably 10% or more. For example, the ratio of the first organic solvent to the total volume of the first organic solvent and the second organic solvent (the volume of the solvent of the electrolyte) ([volume of the first organic solvent] / [volume of the first organic solvent + volume of the second organic solvent]) is preferably 0.1 or more. The overall viscosity of the electrolyte containing the first organic solvent at a volume ratio of 10% or more is low. Therefore, a secondary battery with high low-temperature output performance can be manufactured.
[0101] The electrolyte may further contain a sultone compound. By including a sultone compound in the electrolyte, a coating film can be formed on the positive electrode and / or the negative electrode during the pretreatment. By covering at least a part of the surface of the active material of the electrode with such a coating film, the surface of the active material can be modified to suppress the reaction between the active material and the electrolyte. As a result, gas generation can be suppressed, and excellent life performance can be exhibited even in a high-temperature environment.
[0102] The concentration of the sultone compound in the electrolyte is preferably 0.1 mass% to 10 mass%, more preferably 0.5 mass% to 5 mass% with respect to the electrolyte. In a secondary battery manufactured in such a manner that the concentration is within the preferred range, an increase in resistance in the electrode due to the formation of an excessive coating film can be suppressed, and at the same time, the effect of suppressing gas generation can be exhibited.
[0103] The sultone compound includes one or more selected from 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and 2,4-butane sultone. The electrolyte may contain one of the above-mentioned sultone compounds or may be mixed with two or more.
[0104] The gel-like non-aqueous electrolyte is prepared by compounding a liquid non-aqueous electrolyte and a polymer material. Examples of the polymer material include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.
[0105] Alternatively, as the non-aqueous electrolyte, in addition to the liquid non-aqueous electrolyte and the gel-like non-aqueous electrolyte, a room-temperature molten salt (ionic melt) containing lithium ions, a polymer solid electrolyte, an inorganic solid electrolyte, etc. can also be used.
[0106] The room-temperature molten salt (ionic melt) refers to a compound that can exist as a liquid at room temperature (15 °C to 25 °C) among organic salts composed of a combination of an organic cation and an anion. The room-temperature molten salts include: a monomer and a room-temperature molten salt existing as a liquid, a room-temperature molten salt that becomes a liquid by mixing with an electrolyte salt, a room-temperature molten salt that becomes a liquid by dissolving in an organic solvent, or a mixture thereof. Generally, the melting point of the room-temperature molten salt used in secondary batteries is 25 °C or lower. In addition, the organic cation generally has a quaternary ammonium skeleton.
[0107] The polymer solid electrolyte is prepared by dissolving an electrolyte salt in a polymer material and solidifying it.
[0108] The inorganic solid electrolyte is a solid substance having Li ion conductivity.
[0109] (4) Separator
[0110] The separator is formed, for example, of a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin non-woven fabric. From the viewpoint of safety, a porous membrane formed of polyethylene or polypropylene is preferably used. This is because these porous films can melt at a certain temperature to cut off the current.
[0111] (5) Outer packaging member
[0112] As the outer packaging member, for example, a container formed of a laminated film or a metal container can be used.
[0113] The thickness of the laminated film is, for example, 0.5 mm or less, preferably 0.2 mm or less.
[0114] As the laminated film, a multilayer film containing a plurality of resin layers and a metal layer interposed between these resin layers is used. The resin layer contains polymer materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). In order to achieve weight reduction, the metal layer is preferably composed of aluminum foil or aluminum alloy foil. The laminated film is sealed by heat fusion bonding and can be formed into the shape of an outer packaging member.
[0115] The thickness of the wall of the metal container is, for example, 1 mm or less, preferably 0.5 mm or less, and more preferably 0.2 mm or less.
[0116] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, its content is preferably 100 mass ppm or less.
[0117] The shape of the outer packaging member is not particularly limited. The shape of the outer packaging member can be, for example, flat (thin), square, cylindrical, coin-shaped, or button-shaped. The outer packaging member can be appropriately selected according to the battery size and the use of the battery.
[0118] (6) Negative terminal
[0119] The negative terminal can be formed of a material that is electrochemically stable and conductive at the Li insertion / extraction potential of the niobium-titanium composite oxide contained in the negative electrode. Specifically, as the material of the negative terminal, copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing at least one element selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si can be cited. The material of the negative terminal is preferably aluminum or an aluminum alloy. In order to reduce the contact resistance with the negative electrode current collector, the negative terminal is preferably composed of the same material as the negative electrode current collector.
[0120] (7) Positive terminal
[0121] The positive terminal can be formed of a material that is electrochemically stable and conductive within a potential range of 3 V to 4.5 V (vs. Li / Li + ). As the material of the positive terminal, aluminum or an aluminum alloy containing at least one element selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si can be cited. In order to reduce the contact resistance with the positive electrode current collector, the positive terminal is preferably formed of the same material as the positive electrode current collector.
[0122] <Powder X-ray diffraction>
[0123] The crystal structure of the compound contained as the active material can be confirmed by powder X-ray diffraction (XRD: X-Ray diffraction). For example, the crystal structures of the niobium-titanium composite oxide and other compounds contained in the negative electrode active material, and the crystal structures of the lithium nickel cobalt manganese composite oxide and other compounds contained in the positive electrode active material can be confirmed by powder X-ray diffraction measurement. As the apparatus for powder X-ray diffraction measurement, for example, SmartLab manufactured by Rigaku Corporation, or an apparatus having an equivalent function thereto is used. The measurement conditions are as follows:
[0124] X-ray source: Cu target
[0125] Power: 45 kV 200 mA
[0126] Soller slit: 5° for both incidence and light reception
[0127] Step size (2θ): 0.02 deg
[0128] Scanning speed: 20 deg / min
[0129] Semiconductor detector: D / teX Ultra 250
[0130] Sample holder: Flat glass sample holder (thickness 0.5 mm)
[0131] Measurement range: 5° ≤ 2θ ≤ 90°.
[0132] <Gas Chromatography-Mass Spectrometry and Viscosity Measurement>
[0133] The composition of the electrolyte and the components in the electrolyte can be quantified by Gas Chromatograph-Mass Spectrometry (GC-MS) measurement. The viscosity of the solvent of the electrolyte can be measured with a rotational viscometer.
[0134] After identifying the composition of the solvent by GC-MS, pure samples are prepared for each component, and the viscosity of each sample is measured with a rotational viscometer. Thus, the viscosity of each component can be known. By combining GC-MS analysis and viscosity measurement in this way, it is possible to confirm the presence or absence of the first organic solvent and the content ratio of the first organic solvent in the electrolyte solvent by using GC-MS.
[0135] Specifically, the measurement can be carried out as follows. First, when the electrolyte to be measured is contained in a battery structure or a secondary battery, the battery outer packaging member is opened under an argon atmosphere, and the electrolyte is taken out. The electrolyte is diluted with dehydrated acetonitrile or the like as needed, and measured by GC-MS. When performing GC-MS measurement, for example, a capillary column manufactured by Frontier Lab Co., Ltd., UACW-30M-0.25F (inner diameter 0.25 mm, length 30 m, film thickness 0.25 μm) is used. After maintaining at 60 °C for 10 minutes, the temperature is raised to 200 °C at a rate of 10 °C / min, whereby the mass spectrum of the electrolyte with each component separated can be obtained. The ionization method is not limited as long as it can be measured. For example, the electron ionization method (Electron Ionization; EI) can be used. In addition, the EI method is sometimes also referred to as the electron impact ionization method. After identifying the electrolyte components by GC-MS, monomer samples of the identified components are prepared, standard curves are made respectively, and each component can be quantified by comparing with the results of GC-MS. In addition, regarding the viscosity, monomer samples of the components identified by GC-MS analysis of the electrolyte are prepared, and the value is obtained by measuring with a rotational viscometer.
[0136] Next, the battery structure used in the manufacturing method of the secondary battery according to the embodiment will be described in more detail with reference to the accompanying drawings.
[0137] Figure 1 It is a cross-sectional view schematically showing an example of the battery structure according to the embodiment. Figure 2 is Figure 1 An enlarged cross-sectional view of part A of the battery structure shown.
[0138] Figure 1 and Figure 2 The battery structure 100 shown includes: Figure 1 The bag-shaped outer packaging member 2 shown, Figure 1 and Figure 2 The electrode group 1 shown and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the bag-shaped outer packaging member 2. The electrolyte (not shown) is held in the electrode group 1.
[0139] The bag-shaped outer packaging member 2 is composed of a laminated film including two resin layers and a metal layer interposed therebetween.
[0140] As Figure 1 shown, the electrode group 1 is a flat wound type electrode group. As Figure 2 shown, the flat, wound type electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.
[0141] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b. In the negative electrode 3, the portion located at the outermost shell of the wound electrode group 1 is as Figure 2 shown, and the negative electrode active material-containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a. On other portions of the negative electrode 3, the negative electrode active material-containing layer 3b is formed on both surfaces of the negative electrode current collector 3a.
[0142] The positive electrode 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b formed on both of its surfaces.
[0143] As Figure 1 shown, the negative electrode terminal 6 and the positive electrode terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative electrode terminal 6 is connected to the portion located at the outermost shell of the negative electrode current collector 3a. In addition, the positive electrode terminal 7 is connected to the portion located at the outermost shell of the positive electrode current collector 5a. The above-mentioned negative electrode terminal 6 and positive electrode terminal 7 protrude outward from the opening of the bag-shaped outer packaging member 2.
[0144] A thermoplastic resin layer is provided on the inner surface of the bag-shaped outer packaging member 2, and the opening of the bag-shaped outer packaging member 2 is closed by thermally melting and bonding it. Whether it is the temporary sealing performed before the process of holding the battery structure 100 in the state where the electrode potential is adjusted, or the formal sealing performed after the process and degassing, for example, the opening of the bag-shaped outer packaging member 2 is closed by thermally melting and bonding. The position where thermally melting and bonding is performed during temporary sealing is, for example, at a position closer to the opening end than the position where thermally melting and bonding is performed during formal sealing.
[0145] The liquid electrolyte can be injected, for example, from the opening of the bag-shaped outer packaging member 2 before temporary sealing. For example, a part of the opening of the bag-shaped outer packaging member 2 is left to be closed by thermally melting and bonding, and the liquid electrolyte is injected through the part that remains un-thermally melted and bonded. Then, the part into which the electrolyte has been injected is closed by thermally melting and bonding to perform temporary sealing.
[0146] The battery structure of the embodiment is not limited to Figure 1 and Figure 2 the battery structure shown in the configuration, and can also be, for example, Figure 3 and Figure 4 the battery shown in the configuration.
[0147] Figure 3 is a partial cutaway perspective view schematically showing another example of the battery structure of the embodiment. Figure 4 is Figure 3 a cross-sectional view of an enlarged portion B of the battery structure shown.
[0148] Figure 3 and Figure 4 The battery structure 100 shown includes:Figure 3 and Figure 4 the electrode group 1 shown in Figure 3 the outer packaging member 2 shown in and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the outer packaging member 2. The electrolyte is held in the electrode group 1.
[0149] The outer packaging member 2 is made of a laminated film including two resin layers and a metal layer interposed therebetween.
[0150] As Figure 4 shown, the electrode group 1 is a stacked-type electrode group. The stacked-type electrode group 1 has a structure in which a separator 4 is sandwiched between a negative electrode 3 and a positive electrode 5 and they are alternately stacked.
[0151] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and negative electrode active material-containing layers 3b supported on both surfaces of the negative electrode current collector 3a. In addition, the electrode group 1 includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and positive electrode active material-containing layers 5b supported on both surfaces of the positive electrode current collector 5a.
[0152] One side of the negative electrode current collector 3a of each negative electrode 3 includes a portion 3c on which no negative electrode active material-containing layer 3b is supported on any surface. This portion 3c functions as a negative electrode current collector tab. As Figure 4 shown, the portion 3c that functions as a negative electrode current collector tab does not overlap with the positive electrode 5. In addition, a plurality of negative electrode current collector tabs (portions 3c) are electrically connected to a strip-shaped negative terminal 6. The front end of the strip-shaped negative terminal 6 is led out to the outside of the outer packaging member 2.
[0153] In addition, although not shown, one side of the positive electrode current collector 5a of each positive electrode 5 includes a portion on which no positive electrode active material-containing layer 5b is supported on any surface. This portion functions as a positive electrode current collector tab. The positive electrode current collector tab, like the negative electrode current collector tab (portion 3c), does not overlap with the negative electrode 3. In addition, the positive electrode current collector tab is located on the opposite side of the electrode group 1 with respect to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is electrically connected to a strip-shaped positive terminal 7. The front end of the strip-shaped positive terminal 7 is located on the opposite side of the negative terminal 6 and is led out to the outside of the outer packaging member 2.
[0154] Refer to Figure 5 and Figure 6 to describe another example of the battery structure. Figure 5 is a cross-sectional view schematically showing another example of the battery structure of the embodiment. Figure 6 is Figure 5 a schematic cross-sectional view of the battery structure shown in along line VI-VI.
[0155] The electrode group 1 is housed in an outer packaging member 2 formed of a rectangular cylindrical metal container. The electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The electrode group 1 has a structure in which the separator 4 is sandwiched between the positive electrode 5 and the negative electrode 3 and wound in a spiral shape to form a flat shape. An electrolyte (not shown) is held in the electrode group 1. As Figure 5 shown, strip-shaped negative electrode leads 16 are electrically connected to multiple locations at the end of the negative electrode 3 located at the end face of the electrode group 1. In addition, strip-shaped positive electrode leads 17 are electrically connected to multiple locations at the end of the positive electrode 5 located at this end face. As Figure 6 shown, the multiple negative electrode leads 16 are connected to the negative terminal 6 in a bundled state. In addition, although not shown, the positive electrode leads 17 are also connected to the positive terminal 7 in a bundled state.
[0156] A metal sealing plate 10 is fixed to the opening of the metal outer packaging member 2 by welding or the like. The negative terminal 6 and the positive terminal 7 are respectively led out to the outside through extraction holes provided in the sealing plate 10. On the inner peripheral surfaces of the respective extraction holes of the sealing plate 10, a negative electrode gasket 8 and a positive electrode gasket 9 are respectively arranged to avoid short circuits caused by contact with the negative terminal 6 and the positive terminal 7. By arranging the negative electrode gasket 8 and the positive electrode gasket 9, the airtightness of the secondary battery can be maintained.
[0157] A control valve 11 (safety valve) is arranged on the sealing plate 10. In the case where the internal pressure in the outer packaging member 2 increases due to gas generated inside the secondary battery, the generated gas can be dissipated to the outside from the control valve 11. Figure 5 In , the control valve 11 is arranged at the center of the sealing plate 10, but the position of the control valve 11 can also be at the end of the sealing plate 10. The control valve 11 can also be omitted.
[0158] In addition, a liquid injection port 18 is provided on the sealing plate 10. The electrolyte can be injected through the liquid injection port 18. After the electrolyte is injected, the liquid injection port 18 can be blocked by a sealing plug 19. The liquid injection port 18 and the sealing plug 19 can also be omitted. When performing temporary sealing before holding the battery structure 100 at the holding temperature in a state where the electrode potential is adjusted, for example, a rubber sealing plug 19 can be used. When performing formal sealing after the treatment and degassing, for example, a sealing plug 19 made of the same material as the sealing plate 10 is used and welded to the sealing plate 10 in a state where the liquid injection port 18 is blocked.
[0159] The manufacturing method of the secondary battery according to the first embodiment includes: maintaining a battery structure including a positive electrode, a negative electrode, and an electrolyte in a processed potential adjustment state, where the processed potential adjustment state is a state in which the positive electrode potential is adjusted within a range of 3.4 V to 3.9 V based on the redox potential of lithium, and the negative electrode potential is adjusted within a range of 1.5 V to 2.0 V based on the redox potential of lithium. The positive electrode contains a lithium nickel cobalt manganese composite oxide. The negative electrode contains a niobium titanium composite oxide. The electrolyte contains one or more first organic solvents with a viscosity of 1 cP or less. The battery structure is maintained at a holding temperature within a range of 50°C to 90°C in the processed potential adjustment state. In this manufacturing method, a secondary battery with high output performance and less gas generation even after repeated charge and discharge cycles can be manufactured.
[0160] [Second Embodiment]
[0161] According to the second embodiment, a secondary battery is provided. This secondary battery is a secondary battery manufactured by the manufacturing method of the first embodiment.
[0162] The secondary battery of the second embodiment is a secondary battery obtained by performing the above-mentioned pretreatment on the battery structure in the manufacturing method of the first embodiment. Therefore, this secondary battery can be, for example, a non-aqueous electrolyte secondary battery or a lithium-ion non-aqueous electrolyte secondary battery.
[0163] Compared with the battery structure that was the precursor of the secondary battery before the electrode potential adjustment described in the first embodiment, except for the state of the product after the pretreatment and the subsequent degassing and formal sealing, the details of the secondary battery of the second embodiment are the same as those of the battery structure described in the first embodiment. That is, the secondary battery of the second embodiment includes the positive electrode, negative electrode, and electrolyte described above in the first embodiment. In addition, the secondary battery of the second embodiment may include the separator, outer packaging member, positive terminal, and negative terminal described above in the first embodiment. Since the details are repetitive, the description is omitted.
[0164] However, in the secondary battery of the second embodiment, compared with the battery structure before the pretreatment, components that can contribute to gas generation such as residual moisture may be in a reduced state. In addition, the battery structure before the pretreatment does not have a coating film on the electrode surface, but in the secondary battery, the positive and negative electrodes may have a coating film on their surfaces. Furthermore, the battery structure before the pretreatment may be in a temporarily sealed state, while the secondary battery is in a state of having been formally sealed.
[0165] The secondary battery of the second embodiment is manufactured by the manufacturing method of the secondary battery of the first embodiment. Therefore, this secondary battery can exhibit high output performance and have less gas generation even after repeated charge and discharge cycles.
[0166] [Embodiment]
[0167] The following describes embodiments, but the implementation mode is not limited by the embodiments described below.
[0168] (Embodiment 1)
[0169] [Fabrication of positive electrode]
[0170] Lithium nickel cobalt manganese composite oxide LiNi 0.5 Co 0.3 Mn 0.2 O 2 as the positive electrode active material, 5 parts by mass of acetylene black as the conductive agent, and 5 parts by mass of polyvinylidene fluoride (PVdF) as the binder are added to N-methylpyrrolidone (NMP) and mixed to prepare a slurry. The slurry is coated on both sides of a current collector composed of aluminum foil with a thickness of 12 μm, and then dried and pressed to fabricate a positive electrode with an electrode density (excluding the current collector) of 3.2 g / cm 3 .
[0171] [Fabrication of negative electrode]
[0172] Monoclinic niobium titanium composite oxide Nb 2 TiO 7 100 parts by mass, 8 parts by mass of acetylene black as the conductive agent, and 8 parts by mass of PVdF as the binder are added to NMP and mixed to prepare a slurry. The slurry is coated on one side of a current collector composed of aluminum foil with a thickness of 12 μm, and then dried and pressed to fabricate a negative electrode with an electrode density (excluding the current collector) of 2.6 g / cm 3 .
[0173] [Fabrication of electrode assembly]
[0174] The positive electrode fabricated above, a separator composed of cellulose with a thickness of 15 μm, the negative electrode fabricated above, and the separator are laminated in this order, and then wound into a vortex shape with the negative electrode located on the outermost periphery to fabricate an electrode assembly. It is heated and pressed at 90 °C to fabricate a flat electrode assembly with a width of 58 mm and a thickness of 3.0 mm. The obtained electrode assembly is housed in an outer packaging member composed of a laminated film with a thickness of 0.1 mm, which is composed of aluminum foil with a thickness of 40 μm and polypropylene layers formed on both sides of the aluminum foil, and vacuum dried at 120 °C for 24 hours.
[0175] [Injection of non-aqueous electrolyte]
[0176] Under an argon atmosphere, propylene carbonate (PC), ethyl methyl carbonate (MEC), and ethyl propionate (EP) were mixed at a volume ratio of 1:1:1 (volume ratio of the first solvent (MEC + EP): 66.7%) to prepare a mixed solvent. In this mixed solvent, lithium hexafluorophosphate (LiPF 6 ) was dissolved at a concentration of 1.0 mol / L. 1,3-Propane sultone (PS) was further added thereto so that the proportion thereof with respect to the whole solution was 1% by mass to prepare a liquid non-aqueous electrolyte (electrolyte).
[0177] The electrolyte thus prepared was injected into the electrode assembly housed in the dried laminate film under an argon atmosphere. Then, the upper part of the laminate film was sealed under reduced pressure to obtain a temporarily sealed secondary battery (battery structure).
[0178] <Aging>
[0179] By charging the temporarily sealed secondary battery to a battery voltage of 1.8 V (SOC 10%) at room temperature (25°C), the positive electrode potential was adjusted to 3.65 V (vs. Li / Li + ), and the negative electrode potential was adjusted to 1.85 V (vs. Li / Li + ). The temporarily sealed secondary battery in the state where the treatment potential was adjusted as described above was heated in a constant temperature bath at a temperature of 80°C (holding temperature, i.e., aging temperature) for 24 hours (holding time, i.e., aging time).
[0180] <Exhaust>
[0181] After heating, the upper part of the temporarily sealed laminate case was opened under an argon atmosphere. Then, the gas was discharged under reduced pressure, and the laminate film was sealed (formally sealed) to obtain a secondary battery.
[0182] (Example 2-11, Comparative Examples 1-5)
[0183] Except that the composition of the electrolyte and the pretreatment conditions were changed as shown in Tables 1 and 2 below, the secondary battery was manufactured according to the same procedure as in Example 1. Regarding the composition of the electrolyte, the composition of the electrolyte solvent, the material type and addition amount of the sultone compound were changed as shown in Tables 1 and 2. Regarding the pretreatment conditions, the positive electrode potential and negative electrode potential adjusted to obtain the treatment potential adjustment state, and the temperature and time of aging (holding temperature and holding time) were changed.
[0184]
[0185]
[0186] [Evaluation]
[0187] <Output Performance Evaluation>
[0188] The internal resistance of the secondary batteries manufactured in each of the examples and comparative examples was measured. A lower internal resistance indicates that higher output performance can be obtained.
[0189] Each secondary battery was charged to 100% SOC in a constant current-constant voltage mode at a charging rate of 1C (the current value that becomes 0% SOC in 1 hour when discharging the battery from 100% SOC) at a temperature environment of 25°C, and then discharged to 50% SOC at a discharge rate of 1C, so as to adjust the depth of discharge (Depth Of Discharge; DOD) to 50%. Then, it was discharged at 10C for 10 seconds, and the internal resistance (resistance value) was calculated from the voltage change and current value in 10 seconds.
[0190] <Cycling performance evaluation>
[0191] For each secondary battery, within the capacity range of 30% to 80% SOC, 1000 cycles of charge and discharge were performed at 70°C, and the gas generation amount was measured.
[0192] Before performing 1000 cycles of charge and discharge, the secondary battery adjusted to DOD 50% according to the same steps as above was submerged in a rectangular parallelepiped-shaped graduated container filled with water, and the volume was read from the change in the water surface position. The volume here is set as V A [cm 3 .
[0193] Next, the secondary battery was fished out of the water. The fished-out secondary battery was subjected to 1000 cycles of charge and discharge in an environment of 70°C within the range of 30% to 80% SOC.
[0194] The battery after the charge and discharge cycle was completed was submerged in a rectangular parallelepiped-shaped graduated container filled with water, and the volume was read from the change in the water surface position. The volume here is set as V B [cm 3 .
[0195] Then, by subtracting the volume V B from the volume V A , the gas generation amount in each secondary battery was calculated.
[0196] The evaluation results of each secondary battery are shown in Table 3 below. Specifically, the internal resistance at 50% SOC and the amount of gas generated during 1000 cycles of charge and discharge are summarized in this table.
[0197] Table 3
[0198]
[0199] Among the secondary batteries manufactured in Examples 1-11, the internal resistance was low, and the amount of gas generated during charge and discharge cycles was also suppressed to a low level. In contrast, the internal resistance of the secondary battery manufactured in Comparative Example 1 was significantly high, and the amount of gas generated in the secondary batteries manufactured in Comparative Examples 2-5 was significantly large.
[0200] In Comparative Example 1, only propylene carbonate (PC) was used as the solvent of the electrolyte. In Comparative Example 1, since the first organic solvent having a viscosity η of 1 cP or less was not contained, the output performance was not improved.
[0201] In Comparative Example 2, when adjusted to the treatment potential adjustment state, the positive electrode potential was higher than 3.9 V (vs. Li / Li + ), and the negative electrode potential was lower than 1.5 V (vs. Li / Li + ). That is, in Comparative Example 2, aging was performed at a relatively high SOC. In Comparative Example 3, aging was performed at a holding temperature exceeding 90°C. In Comparative Examples 2 and 3 above, it was considered that the electrolyte components decomposed due to inappropriate aging conditions, and as a result, the amount of gas generated during high-temperature charge and discharge cycles increased.
[0202] In Comparative Example 4, aging was performed at a holding temperature lower than 50°C. In Comparative Example 4, it was considered that the pretreatment effect was insufficient, and as a result, the amount of gas generated during high-temperature charge and discharge cycles increased.
[0203] As described above, as shown by the evaluation results of the secondary batteries manufactured in the respective examples, by the manufacturing method described in the first embodiment, a secondary battery having high output performance and suppressing gas generation during repeated charge and discharge cycles can be manufactured.
[0204] According to at least one of the above-described embodiments and examples, a method for manufacturing a secondary battery is provided. The manufacturing method includes the following steps: a step of preparing a battery structure including a positive electrode containing a lithium nickel cobalt manganese composite oxide, a negative electrode containing a niobium titanium composite oxide, and an electrolyte containing one or more first organic solvents having a viscosity of 1 cP or less; a step of obtaining a treatment potential adjustment state by adjusting the positive electrode potential while adjusting the negative electrode potential; and a step of maintaining the battery structure in the treatment potential adjustment state at a holding temperature in the range of 50°C to 90°C. In the step of obtaining the treatment potential adjustment state, the positive electrode is adjusted to a potential of 3.4 V (vs. Li / Li + ) to 3.9 V (vs. Li / Li + ) based on the lithium redox potential, and at the same time, the negative electrode is adjusted to a potential of 1.5 V (vs. Li / Li + ) to 2.0 V (vs. Li / Li +The potential of (). According to the above configuration, a manufacturing method of a secondary battery that exhibits high output performance and has little gas generation even when charged and discharged repeatedly, and the secondary battery can be provided.
[0205] Although several embodiments of the present invention have been described, these embodiments are presented only as examples and are not intended to limit the scope of the invention. These new embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention described in the claims and its equivalents.
[0206] In addition, the above embodiments can be summarized into the following technical solutions.
[0207] (Technical solution 1)
[0208] A manufacturing method of a secondary battery, which includes the following steps:
[0209] A step of preparing a battery structure, the battery structure including a positive electrode containing a lithium nickel cobalt manganese composite oxide, a negative electrode containing a niobium titanium composite oxide, and an electrolyte containing one or more first organic solvents having a viscosity of 1 cP or less;
[0210] A step of obtaining a processed potential adjustment state by adjusting the positive electrode potential of the positive electrode to be in the range of 3.4 V to 3.9 V based on the oxidation-reduction potential of lithium and adjusting the negative electrode potential of the negative electrode to be in the range of 1.5 V to 2.0 V based on the oxidation-reduction potential of lithium; and
[0211] A step of maintaining the battery structure in the processed potential adjustment state at a holding temperature in the range of 50 °C to 90 °C.
[0212] (Technical solution 2)
[0213] According to the above technical solution 1, the step of maintaining the battery structure at the holding temperature in the processed potential adjustment state is performed for 6 hours to 72 hours.
[0214] (Technical solution 3)
[0215] According to the above technical solution 1 or 2, the electrolyte contains the first organic solvent in a volume ratio of 10% or more.
[0216] (Technical solution 4)
[0217] According to any one of the above technical solutions 1 to 3, the first organic solvent contains one or more selected from diethyl carbonate, ethyl methyl carbonate, and ethyl propionate.
[0218] (Technical Solution 5)
[0219] According to any one of the above technical solutions 1 to 4, the electrolyte contains a second organic solvent containing propylene carbonate.
[0220] (Technical Solution 6)
[0221] According to any one of the above technical solutions 1 to 5, the electrolyte further contains a sultone compound.
[0222] (Technical Solution 7)
[0223] According to the above technical solution 6, the sultone compound contains one or more selected from 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and 2,4-butane sultone.
[0224] (Technical Solution 8)
[0225] According to any one of the above technical solutions 1 to 7, the lithium nickel cobalt manganese composite oxide contains a compound represented by Li x Ni 1-y- z Co y Mn z O 2 and 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, and y + z < 1.
[0226] (Technical Solution 9)
[0227] According to any one of the above technical solutions 1 to 8, the niobium titanium composite oxide contains a compound represented by Li a Ti 1- b M1 b Nb 2-c M2 c O 7+δ and a compound represented by Li a Ti 1-b M3 b+c Nb 2-c O 7-δ ; in the Li a Ti 1-b M1 b Nb 2-c M2 c O 7+δ , M1 is at least one selected from Zr, Si, and Sn, M2 is at least one selected from V, Ta, and Bi, 0 ≤ a ≤ 5, 0 ≤ b < 1, 0 ≤ c < 2, and -0.3 ≤ δ ≤ 0.3; the Li a Ti 1- bM3 b+c Nb 2-c O 7-δ wherein M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo, 0 ≤ a ≤ 5, 0 ≤ b < 1, 0 ≤ c < 2, and -0.3 ≤ δ ≤ 0.3.
[0228] (Technical solution 10)
[0229] A secondary battery manufactured by the manufacturing method described in any one of the above technical solutions 1 to 9.
Claims
1. A method for manufacturing a secondary battery, comprising the following steps: A step of preparing a battery structure, the battery structure including a positive electrode containing a lithium nickel cobalt manganese composite oxide, a negative electrode containing a niobium titanium composite oxide, and an electrolyte containing one or more first organic solvents having a viscosity of 1 cP or less; A step of obtaining a processed potential adjustment state by adjusting the positive electrode potential of the positive electrode to be in the range of 3.4 V to 3.9 V based on the oxidation-reduction potential of lithium and adjusting the negative electrode potential of the negative electrode to be in the range of 1.5 V to 2.0 V based on the oxidation-reduction potential of lithium; and A step of maintaining the battery structure in the processed potential adjustment state at a holding temperature in the range of 50°C to 90°C.
2. The method for manufacturing a secondary battery according to claim 1, wherein, The step of maintaining the battery structure at the holding temperature in the processed potential adjustment state is performed for 6 hours to 72 hours.
3. The method for manufacturing a secondary battery according to claim 1 or 2, wherein, The electrolyte contains the first organic solvent in a volume ratio of 10% or more.
4. The method for manufacturing a secondary battery according to any one of claims 1 to 3, wherein, The first organic solvent contains one or more selected from diethyl carbonate, ethyl methyl carbonate, and ethyl propionate.
5. The method for manufacturing a secondary battery according to any one of claims 1 to 4, wherein, The electrolyte contains a second organic solvent containing propylene carbonate.
6. The method for manufacturing a secondary battery according to any one of claims 1 to 5, wherein, The electrolyte further contains a sultone compound.
7. The method for manufacturing a secondary battery according to claim 6, wherein, The sultone compound contains one or more selected from 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and 2,4-butane sultone.
8. The method for manufacturing a secondary battery according to any one of claims 1 to 7, wherein, The lithium nickel cobalt manganese composite oxide contains a compound represented by Li x Ni 1-y-z Co y Mn z O 2 , where 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, and y + z < 1.
9. The method for manufacturing a secondary battery according to any one of claims 1 to 8, wherein, The niobium-titanium composite oxide contains at least one monoclinic niobium-titanium composite oxide selected from the compounds represented by Li a Ti 1-b M1 b Nb 2-c M2 c O 7+δ and the compounds represented by Li a Ti 1-b M3 b+c Nb 2-c O 7-δ In the Li a Ti 1-b M1 b Nb 2-c M2 c O 7+δ M1 is at least one selected from Zr, Si, and Sn, M2 is at least one selected from V, Ta, and Bi, 0 ≤ a ≤ 5, 0 ≤ b < 1, 0 ≤ c < 2, and -0.3 ≤ δ ≤ 0.3; in the Li a Ti 1-b M3 b+c Nb 2-c O 7-δ M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo, 0 ≤ a ≤ 5, 0 ≤ b < 1, 0 ≤ c < 2, and -0.3 ≤ δ ≤ 0.
3.
10. A secondary battery manufactured by the manufacturing method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for manufacturing non-aqueous electrolyte secondary battery
CN105164847A
Manufacturing method of nonaqueous electrolyte secondary battery
JP2012079561A